Mothers' Physiological and Affective Responding to Infant Distress: Unique Antecedents of Avoidant and Resistant Attachments. Issue 2 (21st August 2017) - Groh, Ashley M.; Propper, Cathi; Mills‐Koonce, Roger; Moore, Ginger A.; Calkins, Susan; Cox, Martha
Abstract : In a sample of 127 mother–infant dyads, this study examined the predictive significance of mothers' physiological and observed emotional responding within distressing and nondistressing caregiving contexts at 6 months for infant attachment assessed with Fraley and Spieker's (2003) dimensional approach and the categorical approach at 12 months. Findings revealed that a lesser degree of maternal respiratory sinus arrhythmia withdrawal and higher levels of maternal neutral (vs. positive) affect within distressing (vs. nondistressing) caregiving contexts were distinctive antecedents of avoidance versus resistance assessed dimensionally (but not categorically), independent of maternal sensitivity. Discussion focuses on the usefulness of examining mothers' physiological and affective responding, considering the caregiving context, and employing the dimensional approach to attachment in identifying unique antecedents of patterns of attachment insecurity.